1994
DOI: 10.1101/gad.8.18.2227
|View full text |Cite
|
Sign up to set email alerts
|

Long-term genome stability and minimal genotypic and phenotypic alterations in HPV16 E7-, but not E6-, immortalized human uroepithelial cells.

Abstract: Paiameteis of genome instability and morphological alterations associated with cell transformation were studied in an isogeneic set of clonal human uroepithelial cell (HUG) lines immortalized by the human papilloma virus 16 (HPV16) E6 and/or E7 gene(s). HPV16 E6 binds p53, leading to rapid degradation of p53, whereas E7 binds and alters pRb and other proteins. We report that two independent E7-immortalized HUG lines showed minimal phenotypic or genotypic alterations, except that both lines contained amplificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
99
0
2

Year Published

1996
1996
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 54 publications
14
99
0
2
Order By: Relevance
“…We observed that two independent E7-transformed HUCs had a clonal marker containing extra 20q material. We also observed that the clonal marker chromosome containing the extra chromosome 20 material remained stable in culture, as did the whole karyotype (Rezniko et al, 1994). Immortalization of E6-transformed HUCs was also associated with chromosome alterations.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…We observed that two independent E7-transformed HUCs had a clonal marker containing extra 20q material. We also observed that the clonal marker chromosome containing the extra chromosome 20 material remained stable in culture, as did the whole karyotype (Rezniko et al, 1994). Immortalization of E6-transformed HUCs was also associated with chromosome alterations.…”
Section: Introductionmentioning
confidence: 52%
“…In four E7-HUCs, dE7-1, eE7-1, gE7-1, and yE7-1, cytogenetic analysis indicated that the clonal marker contained 20q material (Table 1). The clonal marker in the two lines previously analysed (i.e., aE7-1 and aE7-2) also contained 20q material by FISH analysis (Rezniko et al, 1994). One of the new lines, yE7-1, contained four clones by cytogenetic analysis, and each of the four clones had an extra copy of chromosome 20 or 20q.…”
Section: Association Of 20q Gain With Immortalization Of E7 Transformmentioning
confidence: 84%
See 2 more Smart Citations
“…Ampli®cation of chromosome 20q DNA has been detected in colon and bladder cancer cells by CGH technique . 20q ampli®cation has also been reported to accompany human papilloma virus 16/E7 mediated transformation of human uroepithelial cells which undergo immortalization and polyploidization at early passages (Rezniko et al, 1994). In addition to these molecular cytogenetic data, elevated copy number of chromosome 20 has been implicated in several cancer cell types based on their karyotypic analyses.…”
Section: Discussionmentioning
confidence: 98%